Molecular modeling identification of key secondary metabolites from xylopia aethiopica as promising therapeutics targeting tssential measles viral proteins (2023)
This study computationally screened three key compounds (vanillin (VAN), oxophoebine (OPB), and dihydrochalcone (DHC)) derived from Xylopia aethiopica (Guinea pepper), a medicinal plant with known antiviral activity, against key druggable measles virus (MV) proteins (fusion protein (FUP), haemagglutinin protein (HMG), and phosphoprotein (PSP)). Each molecular species was subjected to a 100 ns molecular dynamics (MD) simulation following docking, and a range of postdynamic parameters including free binding energy and pharmacokinetic properties were determined. The docking scores of the resulting OPB-FUP (-5.4kcal/mol), OPB-HMG (-8.1 kcal/mol), and OPB-PSP (-8.0kcal/mol) complexes were consistent with their respective binding energy values (-25.37, -28.74, and -40.68 kcal/mol), and higher than that of the reference standard, ribavirin (RBV) in each case. Furthermore, all the investigated compounds were thermodynamically compact and stable, especially HMG of MV, and this observation could be attributed to the resulting intermolecular interactions in each system. Overall, OPB may possess inhibitory properties against MV glycoproteins (FUP and HMG) and PSP that play important roles in the replication of MV and measles pathogenesis. While OPB could serve as a scaffold for the development of novel MV fusion and entry inhibitors, further in vitro and in vivo evaluation is highly recommended.